2015
DOI: 10.11114/jets.v3i5.999
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Environments of Preschool Education Classrooms in Turkey: The Case of Muğla

Abstract: This study examined the quality of the literacy environments of 17 public preschool classrooms in Muğla, Turkey through detailed observations using the OMLIT-CLOC, an inventory of classroom literacy resources that identifies and rates 11 aspects of the literacy environment on a scale from 1 (low) to 3 (high). The results indicated the literacy environments of preschool classrooms in Muğla-including print displays, books, writing and reading areas and listening materialsto be of low-to-moderate quality. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
1
0
2
Order By: Relevance
“…Although in the other half of the classrooms, pre-reading activities were observed, these activities were commonly limited to pointing to features of the book such as the title and illustrations, calling attention to the books they have read before and linking the book to the children's previous activities outside of class (for example, before reading a book on giraffes, the teacher reminded the visit they had to the zoo previously). These findings are in accordance with previous studies indicating that teachers do not spend sufficient time on pre-reading setting up activities and in general, reading alouds appear to be a stand-alone routine of the day without being part of other classroom activities or experiences (Damber, 2015) and suggest that in order to attract children's interests, reading areas need to be organized to be more physically and visually inviting to children (Justice, 2006;Kraemer, McCabe, & Sinatra, 2012;Roskos & Neumann, 2001;Tarım, 2015;Vukelich, Christie, & Enz, 2012) and pre-reading activities should be intellectually stimulating.…”
Section: Discussionsupporting
confidence: 81%
“…Although in the other half of the classrooms, pre-reading activities were observed, these activities were commonly limited to pointing to features of the book such as the title and illustrations, calling attention to the books they have read before and linking the book to the children's previous activities outside of class (for example, before reading a book on giraffes, the teacher reminded the visit they had to the zoo previously). These findings are in accordance with previous studies indicating that teachers do not spend sufficient time on pre-reading setting up activities and in general, reading alouds appear to be a stand-alone routine of the day without being part of other classroom activities or experiences (Damber, 2015) and suggest that in order to attract children's interests, reading areas need to be organized to be more physically and visually inviting to children (Justice, 2006;Kraemer, McCabe, & Sinatra, 2012;Roskos & Neumann, 2001;Tarım, 2015;Vukelich, Christie, & Enz, 2012) and pre-reading activities should be intellectually stimulating.…”
Section: Discussionsupporting
confidence: 81%
“…A study conducted by Justice, Kaderavek, Fan, Sofka & Hunt (2009) also found that storybook reading in the classroom can positively affect children's knowledge in simple writing and their conception towards print. Even though the way storybook reading is carried out might vary in different countries, it consistently shows the similar importance of storybook reading in children's early literacy development (Bay & Cetin, 2014;Cetin & Bay, 2015;Tarim, 2015).…”
Section: Socio-culture Picture Books and Children's Literacymentioning
confidence: 99%
“…Bununla birlikte bu araştırmadaki çocukların yazı kavramlarını ölçen maddelerdeki başarı yüzdelerinin Amerikalı çocuklarınkine kıyasla daha düşük olduğu görülmektedir (Justice ve Ezell, 2001;Justice vd., 2006a). Her ne kadar Okul Öncesi Eğitimi Programı'nda (MEB, 2013) yazı farkındalığına ilişkin kazanım ve buna ilişkin göstergeler yer alsa da bu durum, okul öncesi öğretmenlerinin yazı farkındalığını destekleyecek nitelikli bir sınıf ortamı oluşturma (Tarım, 2015) ve buna ilişkin uygulamalara yer verme (Ergül, Akoğlu, Sarıca, Tufan ve Karaman, 2015) açısından yetersiz kalmalarının bir sonucu olabilir.…”
Section: Kendiliğinden Ortaya çıKan Okuryazarlık Becerilerinin Yaşa Gunclassified
“…Belirtilen bu bulgular, Okul Öncesi Eğitimi Programı'nda (MEB, 2013) çocukların kendi isimlerini görsel olarak tanımaları, duygu ve düşüncelerini yetişkine yazdırmaları şeklinde göstergeler bulunmasına rağmen öğretmenlerin çocukları kendileri için yazı yazmaya teşvik etmesi için göstergeler içermemesinden ve bunun doğal bir sonucu olarak öğretmenlerin bu tür uygulamalara yer vermemesinden kaynaklanıyor olabilir. Ayrıca, okul öncesi eğitim kurumlarının sınıflarında genellikle yazı yazma için ayrı bir alanın ve ilgili malzemelerin olmaması ve çocukların yazı yazma araçlarına öğretmenin planladığı etkinler dışında erişimlerinin olmaması da diğer bir neden olarak gösterilebilir (Tarım, 2015).…”
Section: Kendiliğinden Ortaya çıKan Okuryazarlık Becerilerinin Yaşa Gunclassified